Results of early panretinal laser coagulation in patients with type 1 diabetes mellitus - Dmitriy Sergeevich Atarshchikov; Vladimir Yur'evich Evgrafov; Yury Evgen'evich Batmanov (Сахарный диабет)
Aim. To evaluate results of panretinal laser coagulation (PLC) for severe non-proliferative and early proliferetaive diabetic retinopathy (DR) in patientswith type 1 diabetes mellitus (DM1). Materials and methods. 58 patients with DM1 were observed. All of them were treated by panretinal laser coagulation after subtenon administrationof triamcinolone (40 mg) under ultrasonic control. Results. PLC at the stage of severe non-proliferative DR stabilized its development in 35% of the patients and caused its reverse development withresolution of oedema and intraretinal hemorrhage, normalization of vein diameter, and improvement of visual acuity in 30%. In 35% of these casesPLC caused neovascularization within 1.6?0.9 years after treatment. Reverse development of DR after PLC was documented in 46.3% cases withearly proliferative DR but stabilization of DR occurred rarer than in the previous group (14.6%) and hemorrhage into the vitreous body more frequently(12 cases in 41 and 2 in 40 respectively, p = 0.0007). Patients with severe non-proliferative DR tended to have reduced requirement for vitrectomyafter PLC compared with those having early proliferative DR (1 case of 40 and 6 of 41, p = 0.052).Conclusion: The above results suggest the necessity of early PLC in DM1 patients.